The Application of Resonance-Enhanced Multiphoton Ionization Technique in Gas Chromatography Mass Spectrometry. (12th May 2014) - Li, Adan; Song, Jianzheng; Sun, Yang; Jiao, Tifeng
Abstract : Gas chromatography resonance-enhanced multiphoton ionization time-of-flight mass spectrometry (GC/REMPI-TOFMS) using a nanosecond laser has been applied to analyze the 16 polycyclic aromatic hydrocarbons (PAHs). The excited-state lifetime, absorption characters, and energy of electronic states of the 16 PAHs were investigated to optimize the ionization yield. A river water sample pretreated by means of solid phase extraction was analyzed to evaluate the performance of the analytical instrument. The results suggested that REMPI is superior to electron impact ionization method for soft ionization and suppresses the background signal due to aliphatic hydrocarbons. Thus, GC/REMPI-TOFMS is a more reliable method for the determination of PAHs present in the environment.